Analgesic effects of repetitive transcranial magnetic stimulation on modified 2010 criteria‐diagnosed fibromyalgia: Pilot study. Issue 4 (8th February 2019) - Cheng, Chih‐Ming; Wang, Shuu‐Jiun; Su, Tung‐Ping; Chen, Mu‐Hong; Hsieh, Jen‐Chuen; Ho, Shung‐Tai; Bai, Ya‐Mei; Kao, Nien‐Tzu; Chang, Wen‐Han; Li, Cheng‐Ta
Abstract : Aim: Fibromyalgia is often comorbid with depression, and less than half those patients achieve satisfactory improvement after adequate pharmacological intervention. The investigation of repetitive transcranial magnetic stimulation (rTMS) at left dorsolateral prefrontal cortex for modified‐2010 American College of Rheumatology (ACR) fibromyalgia and major depressive disorder (MDD) is still in its infancy. Methods: In this double‐blind, randomized, sham‐control study, subjects diagnosed with ACR‐2010 fibromyalgia and DSM‐IV‐TR MDD were recruited and received either active or sham interventions for 2 weeks. Hamilton Depression Rating Scale (HDRS) and the 10‐cm visual analogue pain scale were evaluated at baseline, week 1, and week 2. Multivariable generalized estimating equations analysis was performed for the association between depression and pain scores at each checkpoint. Results: Twenty subjects were recruited. There was a significant difference over the 2 weeks between the rTMS and sham stimulation groups ( P = 0.029), but subgroup analyses were further performed due to significant interaction of group and HDRS on pain outcomes ( P = 0.020). The active group had significant improvement in pain at week 2 compared with week 1 ( P = 0.021), but the control group did not have any improvement in pain ( P = 0.585). Of the mild–moderate depression patients, the pain score in the active group was significantly lower than in the sham group at week 1 ( P = 0.001) and at week 2 ( P < 0.001). For the severe depression group, there was significantly lower pain over the 2 weeks in the active group ( P = 0.045) but the sham group had significantly relapsing pain at week 2 ( P < 0.001). Conclusion: Left prefrontal rTMS has an analgesic effect in modified‐ACR 2010‐defined fibromyalgia and MDD patients. Further investigation is required, however, in order to determine how to regulate the different rTMS treatment protocols according to individual baseline depression severity in patients with MDD and fibromyalgia.